2022
DOI: 10.1159/000527566
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Prolonged Antiplatelet Therapy after Percutaneous Coronary Intervention in Chronic Kidney Disease Patients: A Systematic Review and Meta-Analysis

Abstract: <b><i>Background:</i></b> The optimal duration of dual antiplatelet therapy (DAPT) after percutaneous coronary intervention (PCI) is not established in chronic kidney disease (CKD) patients. <b><i>Objective:</i></b> In this meta-analysis, we evaluated the efficacy and safety of long duration DAPT compared with short duration DAPT in CKD patients after PCI. <b><i>Methods:</i></b> We searched PubMed<b>,</b> Cochrane, and Embase t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…However, more data is needed [ 54 ]. One study found that prolonged dual-antiplatelet therapy (DAPT), including cilostazol, might decrease the risk of mortality, MACE, and stroke in patients with chronic kidney disease (CKD) without any significant difference in bleeding or revascularization [ 55 ].…”
Section: Reviewmentioning
confidence: 99%
“…However, more data is needed [ 54 ]. One study found that prolonged dual-antiplatelet therapy (DAPT), including cilostazol, might decrease the risk of mortality, MACE, and stroke in patients with chronic kidney disease (CKD) without any significant difference in bleeding or revascularization [ 55 ].…”
Section: Reviewmentioning
confidence: 99%